Quantitative evaluation of volunteered geographic information paradigms: social location-based services case study. Issue 344 (September 2015) - Dror, T.; Dalyot, S.; Doytsher, Y.
Abstract : As of 2010, 90% of the data that existed in the world were created within the previous 2 years, while personal location data have been singled out as one of the five primary 'big data' streams in the 2011 McKinsey report. By 2020, the volume of existing data will increase by 50-fold, where a large percentage of this volume will be associated with geospatial data. One of the reasons for this is the existence of the volunteered geographic information (VGI) paradigm, which encapsulates the idea of using the Internet (Web 2.0) to create, share, visualise, and analyse geographic information and knowledge. This neogeography revolution has started to fundamentally transform how geographic data are acquired, maintained, analysed, visualised, and consequently used. Thus, it has the potential to influence common practices, since it captures a broad knowledge of the environment we live in, in all aspects of life, encompassing new services to take place, applications and processes to be developed – all of which are location based. The diversity of applications and services that explore the potential of VGI argues for its current usability relevance: ranging from transportation network analysis, to air pollution and air quality, to natural disaster decision-making systems. This revolution has contributed to the development of two important working and knowledge paradigms: Crowdsourcing and Wisdom of the Crowd, widely used today within the mapping and geo-information discipline. Still, both terms are commonly misused and replaced. This paper aims at distinguishing between the terms via the quantitative and theoretical examination of four widely used social location-based services: OpenStreetMap (OSM), Moovit, Waze and Ushahidi. Eight primary characteristics that influence the paradigm of both Crowdsourcing and Wisdom of the Crowd are defined and examined, aiming to investigate and emphasise the differences between the four, namely: diversity, decentralisation, independency, aggregation, knowledge, activity, privacy and exploitation. It was found that OSM is an excellent example of a Crowdsourcing service, while though Ushahidi is considered as a Crowdsourcing service, its characteristics are coupled better with those of Wisdom of the Crowd. Moovit and Waze do not correspond to the Crowdsourcing paradigm, and thus are categorised as Wisdom of the Crowd services.